Isolation and properties of Streptomyces spore membranes. - Quirós, L M (1986)
A simple procedure for the isolation of membranes from Streptomyces spores is described which produces about 12 mg of membrane protein per g of dry weight. The membrane fractions were contaminated by low levels of DNA, RNA, and hexosamines. The functional integrity of the membrane is conserved through the isolation procedure, as evaluated by the presence of several activities of the membrane-bound electron transport chain. This isolation procedure allowed the determination of the biosynthesis of proteins and phospholipids of the membrane. Both biosynthetic processes started in the first 5 min of germination and increased progressively during spore germination. A stable mRNA fraction of the dormant spore encoded 44% of the membrane proteins synthesized early in germination, but most of the phospholipid biosynthesis was not dependent on this fraction.